Comparison between young and adult track and field athletes on oxidative stress markers - Zalavras, A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Reports in the literature suggest that glutathione levels might be different between children and adults (Michelet et al. 1995). Furthermore, glutathione levels were positively correlated with regular physical exercise (Michelet et al. 1995). However, studies comparing the redox status between young and adult individuals are scarce. Therefore, the aim of this study was to compare the antioxidant defense system between young and adult track and field athletes and assess whether it responds differently following an acute bout of aerobic exercise. Methods: Thirteen young athletes (age: 14.2±1.1; weight: 54.2±8.5; height: 165.6±7.4) and 12 adult athletes (age: 25.2±6.9; weight: 66.9±6.1; height: 175.2±4.5) participated in this study. Blood was collected prior to, immediately post and 1h post an acute exercise bout (45 minutes at 70% VO2max). Blood was analyzed for indices of oxidative stress (reduced glutathione) and the antioxidant defense system (total antioxidant capacity). Results: A 2X3 (group X time) repeated measures ANOVA did not reveal significant differences between groups nor an interaction effect. However there was a significant difference across time. Glutathione levels were significantly lower (p<0.05) for both groups immediately post exercise and total antioxidant capacity was significantly elevated (p<0.05) immediately post and 1h post exercise. Discussion: These results indicate that there are no differences in the antioxidant defense system between young and adult track and field athletes. Furthermore, the response to an acute stressor as exercise is similar between the two aged groups.